Rekognisi Hak Cipta atas Karya Seni Gambar yang Dihasilkan Melalui Artificial Intelligence Berdasarkan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Sinaga, Blassyus Bevry (Jurnal Hukum Positum, 2024)
Image artwork is a creation protected by copyright, as regulated in Article 40 of Law Number 28 of 2014 on Copyright. Artificial Intelligence technology that is able to generate images based on user descriptions raises confusion regarding the recognition of image creation under Copyright Law. Artificial Intelligence capable of creating images without a human-like imagination process also facilitates plagiarism. The purpose of this research is to analyze whether images generated by Artificial Intelligence can be recognized for Copyright under the Copyright Act and how legal protection against image plagiarism through Artificial Intelligence. This research method is normative juridical by analyzing primary and secondary legal materials. This research shows that images from Artificial Intelligence can not be recognized as copyrightable works because it does not meet the elements of creation in the Copyright Act. Legal protection against image plagiarism through Artificial Intelligence allows victims to pursue civil, criminal, and corporate liability.